MST1 Promotes Apoptosis through Phosphorylation of Histone H2AX - Wen, Weihong (American Society for Biochemistry and Molecular Biology, 2010)
MST1 (mammalian STE20-like kinase 1) is a serine/threonine kinase that is cleaved and activated by caspases during apoptosis. Overexpression of MST1 induces apoptotic morphological changes such as chromatin condensation, but the mechanism is not clear. Here we show that MST1 induces apoptotic chromatin condensation through its phosphorylation of histone H2AX at Ser-139. During etoposide-induced apoptosis in Jurkat cells, the cleavage of MST1 directly corresponded with strong H2AX phosphorylation. In vitro kinase assay results showed that MST1 strongly phosphory-lates histone H2AX. Western blot and kinase assay results with a mutant S139A H2AX confirmed that MST1 phos-phorylates H2AX at Ser-139. Direct binding of MST1 and H2AX can be detected when co-expressed in HEK293 cells and was also confirmed by an endogenous immunoprecipitation study. When overexpressed in HeLa cells, both the MST1 full-length protein and the MST1 kinase domain (MST1-NT), but not the kinase-negative mutant (MST1-NT-KN), could induce obvious endogenous histone H2AX phosphorylation. The caspase-3 inhibitor benzyloxycarbonyl-DEVD-fluoromethyl ketone (Z-DEVD-fmk) attenuates phosphorylation of H2AX by MST1 but cannot inhibit MST1-NT-induced histone H2AX phosphorylation, indicating that cleaved MST1 is responsible for H2AX phosphory-lation during apoptosis. Histone H2AX phosphorylation and DNA fragmentation were suppressed in MST1 knockdown Jurkat cells after etoposide treatment. Taken together, our data indicated that H2AX is a substrate of MST1, which functions to induce apoptotic chromatin condensation and DNA fragmentation.